Advertising Styles In Embracing Marginal Segmentation: A Cultural Studies Perspective - Pangestu, Perdana Putra (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2024)
The concept of inclusivity, which blurs the idealized concept, is interpreted by brands as embracing marginalized segments of society to increase sales value and brand awareness. This realization emerges in advertising services that prominently feature marginalized segments, represented through actors and specific informational messages. The effectiveness of advertising with such a concept lies in its ability to address the issues faced by marginalized segments through a comprehensive understanding of advertising communication, behavior, and consumer segments. The objective of this article is to explore the advertiser's approach model in embracing marginalized segments, using a qualitative method to track and analyze relevant advertising releases, which are then examined through the lens of cultural studies. The results of this study demonstrate that advertisers adapt to market situations by considering various constructions of identity and the ideas that are currently present and will persist in society.